An Empirical Analysis of Auditor Litigation - Sekar Mayangsari; Bambang Sudibyo (The Indonesian Journal of Accounting Research, 2013)
This study investigates the influence of several factors on probability of litigation against auditor. The factors derived from a theoretical and empirical analyses and economic incentives to bring lawsuit. This study identifies three factors into which cause litigation against auditor can be classified and are as follows: auditee characteristics, auditor characteristics and auditor-auditee relationship characteristics. This study uses logit regression to test the hypotheses. Samples are audit engagement for manufacture public company during 1996-2003. We use purposive sampling and get 171 audit engagements as samples: 78 audit engagement whose auditors are sued and 93 audit engagement whose auditors are not sued during 1996-2003. The results show that client size, management ownership and institutional ownership not significantly influence on probability of litigation against auditors. Other factors, such as: audit committee, independence commissioner, earnings management, conservatism, financial difficulties, firm risk, industry risk, audit quality, the length of auditor engagement and service spectrum significantly influence on probability that auditor will be sued.